Characterization of the gut microbiome in Wuhuang pigs and their crossbred offspring - Yan, Zhijuan; Yang, Yiting; Yu, Xinghong; Hao, Ziling; Du, Yong; Wang, Yan; Wu, Yuanyuan; Zhao, Ye; Niu, Lili; Zhou, Xiaofeng; Shen, Linyuan; Gan, Mailin; et al. (Frontiers in Veterinary Science, 2025)
IntroductionAs an indigenous Chinese breed, Wuhuang pigs are valued for their stress resistance, tolerance to coarse feed, and high lean meat yield, while Berkshire pigs serve as ideal sires due to superior meat quality and early maturity. To explore the microbial basis of hybrid vigor in these breeds, we compared the gut microbiota of purebred Wuhuang pigs and Wuhuang–Berkshire hybrids.MethodsMicrobial composition was assessed via 16S rDNA sequencing, and predictive functional profiling was performed using PICRUSt2 analysis.ResultsHybrids exhibited significantly increased microbial α-diversity and altered β-diversity. Notably, hybrid ceca were enriched with probiotic genera involved in fiber degradation and short-chain fatty acid (SCFA) production—such as Prevotella, Ruminococcus, Lachnospiraceae, and Roseburia—accompanied by a higher Firmicutes-to-Bacteroidetes ratio and strengthened microbial network connectivity. Predictive functional profiling further revealed significantly elevated activity in hybrid pigs for key metabolic pathways including tryptophan synthesis, pyridoxal salvage, and galacturonic acid metabolism (FDR < 0.05).DiscussionThese results imply that hybrid animals leverage enriched probiotic consortia to augment nutrient metabolism and immune function, thereby supporting improved stress resilience and feed efficiency. This study provides potential microbial targets for the future genetic improvement of indigenous pig breeds.